Grandes empreendimentos agroindustriais e evolução de indicadores socioeconômicos: o caso do Polígono Canavieiro Paulista - João Jaime de Carvalho Almeida Filho; Jonathas Magalhães Pereira da Silva; Marcos Roberto Martines (Confins)
The article examines the evolution of socioeconomic and demographic indicators that occurred in the municipalities of the interior of São Paulo, between 1975 and 2018, a period coinciding with the expansion and consolidation of the sugar-energy sector, which uses almost half of the agricultural land in this territory and installs plants in more than a third of the municipalities of what we call Polígono Canavieiro Paulista. Supposedly a generator of economic growth, the phenomenon raises a question: do charges and bonuses result in a positive balance for the municipality where the plants are installed? The present work addresses this question, comparing indicators between groups of municipalities with or without the presence of plants and spatializing results. An attempt is made to verify the influence of the plants at the municipal and regional levels and, in the municipalities with plants, there is a discrete, positive and constant differentiation regarding the evolution of the indicators. Finally, the research allows us to observe that, from the presence of the sugar-energy sector, in the studied period, inequalities are accentuated between the cities of São Paulo.